The government of Hugo Chavez in the political system of modern Venezuela: achievements and failures - G. E. Ludena Lopez; N. A. Omelchenko (Управление)
The article gives the author’s interpretation of the successes and shortcomings in the activities of the Hugo Chavez’s government, which manifested themselves over the 14 years of his reign (1999–2013). Based on the analysis of the political, economic and social background of the time of Chavez’s rule, the authors of the article make a reasonable conclusion about the complexity of the task of developing a certain general criterion for assessing the positive and negative sides of this rule. Liberal democracy, which forms the basis of the political thinking of Chavez’s critics on the right, places great importance on the system of checks and balances, which the Chavistas of the radical democracy model tend to ignore. Another example of different approaches that blur the objective assessment of the activities of the Chavez government are the attitudes of “social prioritization” supporters, who believe that the activities of nationalized companies in strategic industries should be primarily subordinated to social goals and national development, giving priority to “pragmatic decision-making”, which prioritizes the goals of productivity and efficiency within the Chavista movement. The author of the article concludes that, on the one hand, one of the undoubted achievements of the Hugo Chavez’s government is that in the period from 1999 to 2013 Venezuela received the highest oil revenues that any President of Venezuela has ever had, and also a noticeable reduction in poverty in the country, providing the people with greater opportunities to participate in political decision-making. On the other hand, a huge external debt, as well as very mediocre economic and social results in the context of the country’s largest oil income, of course, should be attributed to obvious miscalculations in the activities of the government of Hugo Chavez.